(untitled) (Práxis Educativa, 2021)
Currently, the discussion on the use of Technologies in educational environments has been increasingly present in studies on Education. The use of Technologies in Education is not a recent reality, and the evolution of technological resources has changed in a way that has significantly changed the act of teaching, and Technology is increasingly being recognized, too, as a means of enhancing learning. This work, in close connection between History and Education, aims to present a systematic literature review from a qualitative analysis of journals of the main Portuguese Lyceums on the use of Technology in the educational Portuguese context from early 20th century to the beginning of computerized teaching, framed in an international view, in a cohesive perspective of the use and, above all, of the way of appropriation of technology in Portuguese schools. The main conclusions of this study suggest an introduction of Technology in Portuguese schools that follows its dissemination in other countries, in particular the USA, suggesting, however, a slow dissemination, with an essentially sporadic use, fruit of the scarcity of resources and little focus on teacher training, giving the use of Technology in school a more irregular and playful character rather than an effective integration in pedagogical practices in order to promote the quality of learning. Keywords: History of Education. Educational technology. Evolution of educational technology.